Penggunaan Global System for Mobile (GSM) untuk pemantauan Kebakaran: Kajian Kes di Bangunan LHDN Kluang - Arifin, Azlin Erina; Omar, Roshartini; Sarpin, Norliana; Shafii, Haryati (Research in Management of Technology and Business, 2021)
Unforeseen fire incidents can occur at any time and anywhere. The quality of use and management of fire prevention systems is also the current fire safety status. The Global System for Mobile (GSM) is a mobile frequency communication system of digital mediation and transmission that serves as a transmitter of information to the user’s phone when it receives data that has been programmed only by the desired circuit. However, in Malaysia, the use of GSM is not used holistically. Therefore, this research aims to examine the potential use of the Global System for Mobile (GSM), identify the challenges faced, as well as measures in increasing the use of GSM on alarms and fire monitoring devices in government buildings. To achieve the objectives, this study uses qualitative methods as data collection through semi-structured interviews with building executives, building technicians, and building security managers. This research found that the respondents’ agreement on the potential use of the system used is in terms of the use of less than one minute for the purpose of sending fire information as well as the percentage of the safety of use is at a high level. Respondents also agreed that the challenges obtained were in terms of high-cost utilization and employees did not face any challenges because the management of system utilization was from external parties. Steps in increasing the use of the system are through briefings, courses, and fire drills. In conclusion, this research encourages government building managers to understand the potential and measures to increase the use of GSM systems in fire management to improve issues related to the safety of the use of fire systems in government buildings.